Practical Management of Aggressive B-Cell Lymphomas with CD20×CD3 Bispecific Antibodies (Canadian Hematology Today, 2025)
CD20×CD3 bispecific antibodies (BsAbs) have transformed the therapeutic landscape of relapsed or refractory large B-cell lymphoma (LBCL). By redirecting T cells to target CD20-expressing lymphoma cells, these off-the-shelf agents offer high response rates and durable remissions in patients who previously had limited options, including those who relapse after chimeric antigen receptor T-cell therapy. In Canada, epcoritamab and glofitamab are now approved for patients with LBCL after at least two prior lines of treatment. The combination of glofitamab, gemcitabine, and oxaliplatin has been recently approved for patients with relapsed/refractory diffuse large B-cell lymphoma not otherwise specified LBCL after at least 1 line of therapy and who are ineligible for autologous hematopoietic stem cell transplant. This review provides a practical framework for Canadian hematologists: identifying eligible patients, implementing pretreatment evaluation, safely delivering therapy in inpatient and outpatient settings, and managing toxicities such as cytokine release syndrome and immune effector cell-associated neurotoxicity syndrome. We will also discuss infection prophylaxis, sequencing with cellular therapies, and future directions for BsAbs in earlier treatment lines.